Artemia feeds: a review of brine shrimp production in the Mekong Delta, Vietnam. (14th August 2018) - Le, Tran Huu; Hoa, Nguyen Van; Sorgeloos, Patrick; Van Stappen, Gilbert
Abstract: Seasonal Artemia pond production has been practiced for several decades by rural salt producing communities in the Mekong Delta, Vietnam, with more success than elsewhere in the world. In spite of this success, yields have been stagnating for a long time due to suboptimal feeding conditions. As feeding is one of the most important factors affecting Artemia production, the aim of this article was to review the studies that have been done so far on the development and application of appropriate Artemia feeds and feeding protocols in this area. So far, there are three main approaches. Traditionally, phytoplankton blooming is stimulated by the use of fertilizers in so‐called fertilization ponds. This green water is supplemented by the use of cheap agriculture waste products and chicken manure, directly applied in Artemia ponds. As this technique, however, often results in suboptimal feeding levels and comes with high nutrient charges in pond effluents, recently a formulated feed has been developed specifically for Artemia pond production which allows further increasing production levels. Finally, also the biofloc technology can be applied in Artemia culture by adding tapioca flour or molasses as carbon source to obtain the ratio C/N ≥ 10 in order to stimulate biofloc development as feed for Artemia in ponds. The limitations of the above techniques are discussed. It is envisaged that the future success and further expansion of Artemia pond production, also outside Vietnam, will increasingly be determined by a flexible use of a combination of these techniques.